2022
DOI: 10.7759/cureus.25712
|View full text |Cite
|
Sign up to set email alerts
|

A Complicated Case of Rheumatoid Arthritis in Septic Shock

Abstract: Sepsis is significantly associated with increased mortality among hospitalized patients. Patients can deteriorate rapidly, leading to septic shock (i.e., tissue hypoperfusion and organ dysfunction despite fluid resuscitation that can ultimately require a vasopressor). Patients immunocompromised from medical conditions such as rheumatoid arthritis with multiple joint arthroplasties are at a major risk of increased infections. Equally, medications that impair the immune system's normal function make this clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Several studies have demonstrated the involvement of proinflammatory cytokines in septic shock, and patients receiving standard treatment improve in intensive care units [76,77]; However, this response to treatment depends on the number of organs affected since admission [78] or if it was associated with surgical intervention, site of infection [79,80], burn [81,82], endocarditis [83,84], necrotizing fasciitis [85,86], meningitis [87,88], and septic arthritis [89][90][91]. The active participation of cytokines correlates with severity and prognosis [76].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the involvement of proinflammatory cytokines in septic shock, and patients receiving standard treatment improve in intensive care units [76,77]; However, this response to treatment depends on the number of organs affected since admission [78] or if it was associated with surgical intervention, site of infection [79,80], burn [81,82], endocarditis [83,84], necrotizing fasciitis [85,86], meningitis [87,88], and septic arthritis [89][90][91]. The active participation of cytokines correlates with severity and prognosis [76].…”
Section: Discussionmentioning
confidence: 99%
“…While these signs are commonly present, they should not be required to define shock according to a statement from the European Society of Intensive Care Medicine (ESICM) consensus [ 16 , 17 ]. This is because septic shock has very variable signs and symptoms, depending on which system is affected [ 10 ], and it is associated with many conditions, such as surgical site infection [ 18 ], trauma [ 19 ], burn [ 20 ], endocarditis [ 21 ], necrotizing fasciitis [ 22 ], HIV [ 23 ], pancreatitis [ 24 ], meningitis [ 25 ], septic arthritis [ 26 ], and COVID-19 [ 27 ].…”
Section: Reviewmentioning
confidence: 99%